2011
DOI: 10.1021/es200364u
|View full text |Cite
|
Sign up to set email alerts
|

PBDDs/Fs and PCDDs/Fs in the Raw and Clean Flue Gas during Steady State and Transient Operation of a Municipal Waste Combustor

Abstract: Concentrations of polybrominated dibenzo-p-dioxins, and -dibenzofurans (PBDDs/Fs) and polychlorinated dibenzo-p-dioxins, and -dibenzofurans (PCDDs/Fs), were determined in the pre- and post-air pollution control system (APCS) flue gas of a municipal waste combustor (MWC). Operational transients of the combustor were found to considerably increase levels of PBDDs/Fs and PCDDs/Fs compared to steady state operation, both for the raw and clean flue gas; ΣPBDDs/Fs increased from 72.7 to 700 pg dscm(-1) in the raw, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Previous studies have indicated that during industrial processes PCDD/F emissions change as the conditions change [32][33][34][35][36][37]. Studies on PCN emission variations in industrial processes are scarce.…”
Section: Trends In Concentration As Smelting Stage Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that during industrial processes PCDD/F emissions change as the conditions change [32][33][34][35][36][37]. Studies on PCN emission variations in industrial processes are scarce.…”
Section: Trends In Concentration As Smelting Stage Changesmentioning
confidence: 99%
“…AL1 and AL3 had the highest levels of PCN formation in the FD stage. Studies have indicated that PCDD/Fs can form during the unsteady state in industrial thermal processes [32,37]. At the FD stage, the raw materials melt as a result of fuel combustion.…”
Section: Trends In Concentration As Smelting Stage Changesmentioning
confidence: 99%
“…The Plant1 samples did not have the same congener pattern, the hepta-to octa-brominated PBDF congeners contributing far more than the tetra-to hexa-brominated PBDD/F congeners to the total 2,3,7,8-substituted PBDD/F concentrations. The most abundant congener in the Plant3 samples was OBDF, and the next most abundant were 1,2,3,4,6,7,OBDD,and 1,2,3,4,6,7, The PBDD/F congener profiles in samples from waste incinerators, secondary copper production plants, iron ore sintering plants, and electric arc furnaces (used to produce steel) have previously been found to be dominated by the more brominated PBDFs, particularly OBDF and 1,2,3,4,6,7,8-HpBDF (Wang et al, 2010b;Wyrzykowska-Ceradini et al, 2011;Wang et al, 2015). The PBDD/F congener profiles in our SAl samples were similar to the profiles that have been found in samples from waste incinerators, secondary copper production plants, iron ore sintering plants, and electric arc furnaces, suggesting similar PBDD/F formation mechanisms occur in the processes performed in each of these types of plant.…”
Section: Congener Profiles Of the Pbdd/fs In The Stack Gas Samplesmentioning
confidence: 99%
“…The effects of chlorine content in waste on the formation mechanisms of polychlorinated pollutants, especially PCDD/Fs, have been studied by different authors [13][14][15]. When chlorine content in waste is less than 0.8-1.1%, chlorine can chlorinate the non-substituted phenol to produce chlorophenols, which are important precursors of PCDDs.…”
Section: Introductionmentioning
confidence: 99%